2011
DOI: 10.1007/s11524-010-9540-7
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity-Related Treatment Outcomes among HIV-Infected Adults in the Bronx, NY

Abstract: Aging, HIV infection, and antiretroviral therapy have been associated with increasing rates of chronic comorbidities in patients with HIV. Urban minority populations in particular are affected by both the HIV/AIDS and chronic disease epidemics. Our objectives were to estimate the prevalence of and risk factors for hypertension, dyslipidemia, and diabetes among HIV-infected adults in the Bronx and describe comorbidity-related treatment outcomes. This was a cross-sectional study of 854 HIV-positive adults receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 21 publications
7
50
4
1
Order By: Relevance
“…The prevalence of comorbidities like hypertension, dyslipidaemia and diabetes were lesser when compared to the study by Chu C et al 13 who noticed prevalence rates of 26%, 48% and 13% for hypertension, dyslipidaemia and diabetes respectively, which may be due to differences in the ethnicity and the higher sample size of 854 studied there. Elevation in liver enzyme levels were seen only in less than 10% compared to one-year long study of 142 patients on Tenofovir by Sanchez-Conde M et al 14 which may be due to the nearly 45% prevalence of Hepatitis C in that population.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The prevalence of comorbidities like hypertension, dyslipidaemia and diabetes were lesser when compared to the study by Chu C et al 13 who noticed prevalence rates of 26%, 48% and 13% for hypertension, dyslipidaemia and diabetes respectively, which may be due to differences in the ethnicity and the higher sample size of 854 studied there. Elevation in liver enzyme levels were seen only in less than 10% compared to one-year long study of 142 patients on Tenofovir by Sanchez-Conde M et al 14 which may be due to the nearly 45% prevalence of Hepatitis C in that population.…”
Section: Discussioncontrasting
confidence: 64%
“…Common clinical adverse effects were seen in more proportions in Tenofovir, Lamivudine and Efavirenz regimen considering the fact that there are only 13 Causality Assessment by Naranjo's Scale Causality assessment was done by using both Naranjo's and WHO scale. The assessment by Naranjo's scale showed that out of 178 ADRs 169 (95%) ADR's were possible, 9 (5%) were classified as probable.…”
Section: Fig 2: Distribution Of Common Clinical Adverse Events In Pamentioning
confidence: 99%
“…Despite the fact that the importance of management of non-HIV comorbidities has been recognized (Chu et al, 2011), no studies measured non-HIV outcomes (e.g., blood pressure, cholesterol, and glucose) and only one measured process outcomes related to comorbidity .…”
Section: Discussionmentioning
confidence: 99%
“…An initial step in this process is to define what good quality of HIV care is (Hung & Pradel, 2014). Since the role of non-HIV comorbidity is increasing, researchers and health-care providers need to go beyond HIV-related morbidity in the evaluation of health outcomes (Chu et al, 2011).…”
Section: Implications For Researchmentioning
confidence: 99%
“…La dislipidemia, la lipodistrofia y la resistencia a la insulina son las principales enfermedades que están presentes en estos pacientes 65 . Dados los procesos fisiopatológicos mencionados, estas enfermedades tienen una íntima relación en su historia natural (Ver Figura 2) por lo cual en la mayoría de los pacientes infectados se presentan de manera simultánea y progresiva La dislipidemia asociada al VIH es un problema que se estima se presenta en un 48% y se asocia con aumento en la incidencia de la enfermedad cardiovascular 66 . Los mecanismos que han intentado explicar este fenómeno incluyen incremento en los niveles de citoquinas (TNF e IL-6), disminución de la depuración de los lípidos, y el aumento de la síntesis hepática de lipoproteína de muy baja densidad 65 .…”
Section: Alteraciones Metabólicasunclassified